A survey of IPv6 mobility management in real-time communications - Ong, Bi-Lynn; Hassan, Suhaidi (IEEE Computer Society, 2005)
The number of mobile wireless Internet users is expected to increase in recent years. Consequently, the 32-bit addressing spaces used for mobile Internet protocol version 4(IPv4) is expected to be used up in the near future. Previous works show that mobile LPv4 causes unnecessary load to the mobile Internet. This unnecessary load increases handover latency. In this paper, we firstly discuss the hybrid Internet protocol version 6 (IPv6) mobility management. Hybrid IPv6 mobility management is the combination of fast handover and hierarchical IPv6 mobility managements. We propose the Session Initiation Protocol (SIP) over hybrid IPv6 mobility management to manage the handover process between inter-domain networks. We also propose cellular hybrid IPv6 mobility management to manage the handover process within intra-domain network. We believe that the proposed SIP over hybrid and cellular hybrid IPv6 mobility managements can solve the problem of unnecessary load and decrease the handover latency.